Fidelity to foraging sites after long migrations. Issue 4 (26th December 2019) - Shimada, Takahiro; Limpus, Colin J.; Hamann, Mark; Bell, Ian; Esteban, Nicole; Groom, Rachel; Hays, Graeme C.
Abstract: Patterns of animal movement associated with foraging lie at the heart of many ecological studies and often animals face decisions of staying in an environment they know versus relocating to new sites. The lack of knowledge of new foraging sites means there is risk associated with a decision to relocate (e.g. poor foraging) as well as a potential benefit (e.g. improved foraging). Using a unique long‐term satellite tracking dataset for several sea turtle species, combined with capture–mark–recapture data extending over 50 years, we show how, across species, individuals generally maintain tight fidelity to specific foraging sites after extended (up to almost 10, 000 km) migration to and from distant breeding sites as well as across many decades. Migrating individuals often travelled through suitable foraging areas en route to their 'home' site and so extended their journeys to maintain foraging site fidelity. We explore the likely mechanistic underpinnings of this trait, which is also seen in some migrating birds, and suggest that individuals will forgo areas of suitable forage encountered en route during migration when they have poor knowledge of the long‐term suitability of those sites, making relocation to those sites risky. Abstract : Using satellite tracking in the western Indian Ocean and northern Australia, the authors show that adult green turtles have fidelity to small foraging areas that may be 1, 000s of km from their nesting beach. Individuals often forgo suitable foraging areas encountered during migration, probably because relocation to those sites is risky.